PENERAPAN MANAJEMEN ASET PADA SIKLUS PENGELUARAN DIREKTORAT MANAJEMEN ASET DAN PENGADAAN UNIVERSITAS SURABAYA - Bella Yolanda Agrevina; Adhicipta Raharja Wirawan (CALYPTRA, 2018)
Abstract - This fieldwork report is prepared to know the implementation of asset management on the expenditure cycle of the Directorate of Asset and Procurement Management of Universitas Surabaya (MAP UBAYA), related to the procurement of goods, goods bill, and labeling of goods. This field work report aims to describe the activities of the author during an internship at the Directorate of MAP UBAYA. The field work report data is obtained from the author's experience during the internship, which is derived from documents and information from employees involved in the spending cycle, such as the Procurement Team and Asset Management Officer. This report specifically discusses the comparison of practices and procedures, the application of asset management theory and its control to the spending cycle at the Directorate of MAP UBAYA. Comparative results between practices and procedures identify not much of a majority difference because all activities are integrated by UBAYA's online system. While the results of the application of asset management theory and its control between identification practices have been applied well. With this apprentice the writer can develop soft skill and hard skills.